If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -8x = 14 + 4x Solving 26 + -8x = 14 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 26 + -8x + -4x = 14 + 4x + -4x Combine like terms: -8x + -4x = -12x 26 + -12x = 14 + 4x + -4x Combine like terms: 4x + -4x = 0 26 + -12x = 14 + 0 26 + -12x = 14 Add '-26' to each side of the equation. 26 + -26 + -12x = 14 + -26 Combine like terms: 26 + -26 = 0 0 + -12x = 14 + -26 -12x = 14 + -26 Combine like terms: 14 + -26 = -12 -12x = -12 Divide each side by '-12'. x = 1 Simplifying x = 1
| -2.68=x-1.9-1.3x | | -3(2x+3)=12 | | 6+x=44 | | 4[6-1(1+2m)]+10m=2(10-3m)+8m | | x^3+bx^2+cx+d=0 | | 6(3+6x)-2=88 | | 7x+8=5x | | -0.9n-1.49n=2.151 | | 2x+12=2y-1 | | b^2+7b+6=-6 | | xy3/x | | -0.9-1.49n=2.151 | | 2(2x+1)=17 | | y^2/3-25/64=0 | | 2.1(6x/3-4.7)=8.66 | | 3a^2=-16+16a | | 11m+4(m-3)+6m=4m-12 | | [y+2]=3 | | 2/300 | | 6x^2-21x-18= | | 0=(x-2)(x-i)(x+i)(x-1-i)(x+1+i) | | f(x)=(x-2)(x-i)(x+i)(x-1-i)(x+1+i) | | 2.1(6x/3-4.7)=20 | | 192/6 | | 2(-1-3)(-1-3)(-1-3)-5= | | 87/3 | | 8+16p=16p+8 | | (4cos^2(x)-2)(3cos^2(x))=0 | | 1x*20x=0 | | 4x^2+y^2+4y=0 | | -6y+10=6y+26 | | T=2π√(l/9) |